IMPLEMENTATION OF THE HAMMING CODE METHOD IN BIT DATA IMPROVEMENT TRANSMISSION PROCESS - Achmad Fauzi; Rizka Putri Rahayu (STMIK KAPUTAMA, 2021)
In a communication system, the success of delivering information from the sender (transmitter) to the receiver (receiver) depends on how accurately the receiver can receive the transmitted signal properly and correctly. In fact, there are still a lot of errors received in the information signal so that data is corrupted (bit error) which is caused by noise (nuisance signal) during the data transmission process, causing the file to be unreadable. Therefore, technology is needed to correct the error in the bit error, namely using the Hamming code method. Hamming code is a simple type of linear error correcting code and is widely used in electronic equipment. Hamming code method works by inserting several check bits into the data. The number of check bits to be inserted depends on the length of the data. Hamming code uses Ex-OR (Exclusive OR) operations in the process of detecting and correcting errors.